Effect of Woody Peat as an Additive on Maturity and Gaseous Emissions During Pig Manure Composting. Issue 2 (3rd April 2019) - Yuan, Jing; Zhang, Difang; Du, Longlong; Yang, Fan; Li, Guoxue; Luo, Yuan
Abstract: Woody peat was used as an additive to compost with pig manure in 1.2 m 3 composting reactors under aerobic conditions for a 77 days period to estimate the effect on the compost maturity and gaseous emissions (NH3, N2 O, and CH4 ). Pig manure was also composted with cornstalks (the traditional method) as a control treatment. The results showed that both cornstalks and woody peat composts reached the required maturity standard. Composting with woody peat as a bulking agent was found to reduced NH3 emissions by 36% than the cornstalks amended treatment. Although CH4 emission increased by adding woody peat, N2 O emission was considerably reduced, resulting in a slight decrease in total greenhouse gas emissions. More importantly, woody peat could reduce the losses of total carbon and total nitrogen, improve the compost quality as fertilizer.